New species of Ameletus Eaton, 1885 from the Russian Far East with notes on Ameletus camtschaticus Ulmer 1927 (Ephemeroptera: Ameletidae) - Tiunova, Tatiana M.; Semenchenko, Aleksandr A.; Velyaev, Oleg A. (Zootaxa, 2017)
The male imagoes, larvae, and eggs of Ameletus allengaensis sp. nov. and Ameletus sirotskii sp. nov. from the Russian Far East are described. Based on the structure of the male genitalia, the imago and larvae of A. allengaensis sp. nov. and A. sirotskii sp. nov. are similar to those of A. camtschaticus, but the discovery of these new species and separation from A. camtschaticus were confirmed by studies of the morphology of the larvae and male imago, as well as molecular analysis. Identity of various developmental stages of the new species were confirmed by analysis of the mitochondrial gene cytochrome oxidase 1 (COI) DNA barcode, which was also used to reconstruct the phylogenetic relationships within the genus Ameletus. The intraspecific sequence divergence based on the Kimura-2-parameter (K2P) distance ranged from 0.0–2.5%, whereas the interspecific sequence divergence based on the K2P distance ranged from 6.2–7.9% within A. sirotskii sp. nov., A. allengaensis sp. nov. and A. camtschaticus. Male imagoes of A. allengaensis sp. nov., A. sirotskii sp. nov., and A. camtschaticus can be distinguished by the size and location of small denticles on the ventral plate of the penis. The larvae of A. allengaensis sp. nov. differ from those of A. sirotskii sp. nov. by the size of gills I and II. In A. allengaensis sp. nov., gill I is almost twice as small as gill II; in A. sirotskii sp. nov., gill I is only slightly smaller than gill II. Both new species differ from A. camtschaticus by gill II, which does not have an anal rib on the anal margin.